1997
DOI: 10.1002/pro.5560060302
|View full text |Cite
|
Sign up to set email alerts
|

Automatic identification and representation of protein binding sites for molecular docking

Abstract: Molecular docking is a popular way to screen for novel drug compounds. The method involves aligning small molecules to a protein structure and estimating their binding affinity. To do this rapidly for tens of thousands of molecules requires an effective representation of the binding region of the target protein. This paper presents an algorithm for representing a protein's binding site in a way that is specifically suited to molecular docking applications. Initially, the protein's surface is coated with a coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
130
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(139 citation statements)
references
References 14 publications
4
130
0
1
Order By: Relevance
“…Surflex (Tripos, St. Louis, MO) is similar to FlexX in that a molecule is first fragmented, and the conformations of each piece are further explored. Here, a "protomol," an idealized active site ligand comprising a cluster of molecular fragments featuring the binding pocket surface (Ruppert et al, 1997), is generated and serves as a target for alignment of fragment conformations based on the molecular similarity method (Jain, 2003). An entire molecule is then assembled by the incremental construction approach (Welch et al, 1996) or a genetic algorithm called the "Whole Molecule Algorithm" (Jones et al, 1997).…”
Section: Principal Component Analysis Of Scut Database Molecules Andmentioning
confidence: 99%
“…Surflex (Tripos, St. Louis, MO) is similar to FlexX in that a molecule is first fragmented, and the conformations of each piece are further explored. Here, a "protomol," an idealized active site ligand comprising a cluster of molecular fragments featuring the binding pocket surface (Ruppert et al, 1997), is generated and serves as a target for alignment of fragment conformations based on the molecular similarity method (Jain, 2003). An entire molecule is then assembled by the incremental construction approach (Welch et al, 1996) or a genetic algorithm called the "Whole Molecule Algorithm" (Jones et al, 1997).…”
Section: Principal Component Analysis Of Scut Database Molecules Andmentioning
confidence: 99%
“…We also showed that magnolol binds to the p38 kinase. The p38 kinase is an important mediator of stress-induced gene expression [21]. In particular, the p38 kinase is known to play a key role in LPS-induced signal transduction pathways leading to cytokine synthesis [15].…”
Section: Discussionmentioning
confidence: 99%
“…The molecule was fully minimized with GasteigerHückel charges. Docking study was performed using Surflex-Dock module of SYBYL 8.1, which uses empirical scoring function using protomol [21].…”
Section: Olecular Docking and Pose Generationmentioning
confidence: 99%
“…The ProtoMol is not meant to be an absolute docking envelope but its purpose is to direct the initial placement of the ligand during the docking process. Docked ligands are scored in the context of the receptor, not in the context of the ProtoMol [45]. To evaluate this docking technique with the C-BS, we used Surflex-Dock to dock selected inhibitors, namely T138067, ABT-751, colchicine and TN-16, as extracted from their X-ray structure in complex with the C-BS (protein data bank (PDB): 3HKE [46] for T138067, 3HKC [46] for ABT-751, 1SA0 [47] for colchicine and 3HKD [46] for TN-16) into the corresponding receptor binding site in silico (Figure 2).…”
Section: Assessment Of the Surflex-dock™ Technique As Applied To The mentioning
confidence: 99%